К экологии черного стрижа (Apus apus L.) - Лошаков, А.С. (Вестник зоологии, 1969)
The martlets come flying on April 30 — May 2 in the Nothern Azov area. The period of reproduction in the Azov area (Berdyansk) includes June—July, but some martlets hatch nestlings in August — the first half of September. Birds lost eggs or nestlings in June or July lay eggs repeatedly and hatch them. The parents feed nestlings (after mass migration of martlets) three times a day: twice in the morning and once i/i the evening and fly somewhere in the afternoon.
The martlets migrate from the Northern Azov area more often on August 25 (mass migration) and a small number of birds whose nestlings cannot fly migrate later. The martlet migration continues till September 15.